Taking sides : (McGraw-Hill, 2007)
This edition of Taking sides: Clashing views on environmental issues contains 38 readings arranged in pro and con pairs to form 19 issues. For each issue, an introduction provides historical background and a brief description of the debate. The postscript after each pair of readings offers recent contributions to the debate, additional references, and sometimes a hint of future directions. Each part is preceded by an On the internet page the lists several links that are appropriate for further pursuing the issues in that part.